Building Energy Analysis of a School Building using Revit - Chuah, Keng Hoo; Muhammad Alwi, Abd Wahab (INTI International University, 2020)
Global warming and environmental issues have driven the demand for high efficient buildings. The integration of Building Information Modelling (BIM) and energy assessments tools to the construction process have contributed to proper selection of building materials and significant reduction in energy consumption. With BIM, the energy consumption is an integrated part of a building design, where energy analyses begin at the conceptual stage of the project. This study considers an energy analysis of a school building located in Spain. The building is an object of study in an inter-university project between INTI International University and another Spain university in 2018. Upon the completion of that project, the authors become interested in the energy usage of the building, which has not been completed then. The new analysis uses Autodesk Revit to develop a Building Performance Analysis (BPA) and to predict its energy performance, including the consideration of building materials and weathering effects. The analysis is able to estimate the CO2 emission, cooling and heating loads, and the electrical usage of the building. With a single and modern workstation, an engineer can carry out the complete analysis of a small building with ease.